Self-regulation of Shadow Teacher for Autism Children in Sekolah Luar Biasa (SLB) Khusus Autis Permata Hati Manado - Tiwa, Tellma Monna; Mandang, Jofie Hilda; Kumaat, Theophany Deasinatalia; Panambunan, Marcella Jeisyra (Proceeding of International Conference on Special Education in South East Asia Region, 2022)
This is a qualitative research that wanted to know about the Self-Regulation of Shadow Teacher for Autism Children especially for those who teach ini Sekolah Luar Biasa (SLB) Khusus Autis Permati Hati Manado. The role of shadow teacher is important in the process of learning for children with autism, because one teacher can't help more than one student. The subject in this research are 2 shadow teachers that help autism children during their time at school. In general the result shows that they both have the concept of working, self-understanding, have enough self-control, but they both have lack of avoiding crisis ability. They realize that they are often affected by the situation and people around them and it's also affected how they work at school. The ability of self-regulation can help them to manage their work and life balance so it will not bring negative effect on each side.